PTH-223 Evaluation of bioelectrical impedance testing in hospital in-patients. (22nd June 2015) - Player, E; Forbes, A
Abstract : Introduction: Assessment of nutritional status in the clinical setting is difficult and often poorly achieved. Bioelectrical impedance analysis (BIA)-derived phase angle (PA) is a simple and non-invasive tool which refines the determination of nutritional status, reflects body cell health, and has prognostic value. However BIA is not much used in clinical practice because of protocols which oblige the patient to be starved and on bed-rest. The research underpinning these protocols is dated and insecure; thus the restrictions may not be necessary. Method: Aim: To determine whether eating and exercise affect BIA-derived Phase Angle. Methods: BIA measurements (Bodystat Quadscan 4000) were made on 17 in-patients who were starved and rested. It was then repeated on two occasions: following exertion and after eating breakfast. Inclusion Criteria – Adult in-patients with capacity to consent. Exclusion Criteria – Nil by mouth, pregnancy, too unwell or otherwise unable to exercise. Statistical analysis SPSS: Wilcoxon signed-rank test for non-parametric data. Results: PA measurements were typical of a hospital patient cohort. Neither exercise nor eating made a statistically nor clinically significant difference to the PA mean PA= 4.312, mean PA= 4.376, (pre-exercise and food vs. post-exercise: p = 0.057), mean PA= 4.335 (pre-exercise and food vs. after food: p = 0.651) Conclusion: In summary, the current protocols of starving and resting patients appear unnecessary and outdated (with due recognition of our small sample size). It is probable that PA measurement is a practical means to improve assessment of nutritional status in hospitalised patients. Disclosure of interest: None Declared.